Analisis Kemandirian Belajar Siswa Sekolah Dasar - Zulaiha, Siti; Meldina, Tika; Ariani, Yulisti (AR-RIAYAH: Jurnal Pendidikan Dasar, 2023)
The background of this research is that student learning independence in thematic learning at SDN 125 Rejang Lebong is a major part of the problems students face in learning due to the lack of student independence in carrying out thematic learning. So the teacher seeks to foster an attitude of independence in students so that in the future they do not always depend on others in learning. The purpose of this study was to find out how students’ learning independence in class IV thematic learning at SDN 125 Rejang Lebong and to find out how the teacher’s efforts foster student learning independence in thematic learning at SDN 125 Rejang Lebong. This type of research used is qualitative in nature. The subjects of this study were the principal, class teachers and students at SDN 125 Rejang Lebong. Sources of data obtained from primary data and secondary data. Data collection techniques through interviews, observation and documentation. Then data analysis techniques using data collection, data reduction, data presentation, tools and conclusions as well as testing the validity of the data using source and technique triangulation. The results of this study indicate that first, student learning independence in class IV thematic learning at SDN 125 Rejang Lebong, students already have an attitude of independent learning in thematic learning. It can be seen that when the thematic learning process is taking place students appear confident, disciplined in learning, active in participating in learning and responsible in learning. Second, the teacher’s efforts to foster student learning independence in thematic learning, namely by providing motivation in learning activities, the teacher does this by telling stories, questions and answers, riddles, giving examples of realities or experiences that occur in life. The teacher creates fun learning by using a variety of methods and using learning resources by utilizing the environment, theme books, the internet and teaching aids in schools.